2019
DOI: 10.1093/jjco/hyz069
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib versus hepatic arterial infusion chemotherapy for advanced hepatocellular carcinoma: a systematic review and meta-analysis

Abstract: Our meta-analysis showed hepatic arterial infusion chemotherapy provided better tumor response and survival benefits than Sorafenib for advanced hepatocellular carcinoma and should be recommended as an alternative treatment option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 33 publications
2
30
1
Order By: Relevance
“…Through systematic literature retrieval, a total of 5 articles were included in this study. Different from the conclusion of previous systematic reviews [27][28][29], the study showed that sorafenib could prolong the overall survival of patients with TACE-refractory HCC compared with HAIC (HR = 1.69, 95% CI [1.09, 2.62], p=0.018). Although the ORR of the HAIC group was significantly higher than that of the sorafenib group (RR = 3.08, 95%CI [1.38, 6.87], p=0.006), the DCR between the HAIC group and the sorafenib group was not significantly different (RR = 0.94, 95%CI [0.60, 1.48], p=0.798).…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…Through systematic literature retrieval, a total of 5 articles were included in this study. Different from the conclusion of previous systematic reviews [27][28][29], the study showed that sorafenib could prolong the overall survival of patients with TACE-refractory HCC compared with HAIC (HR = 1.69, 95% CI [1.09, 2.62], p=0.018). Although the ORR of the HAIC group was significantly higher than that of the sorafenib group (RR = 3.08, 95%CI [1.38, 6.87], p=0.006), the DCR between the HAIC group and the sorafenib group was not significantly different (RR = 0.94, 95%CI [0.60, 1.48], p=0.798).…”
Section: Discussioncontrasting
confidence: 96%
“…Previous studies suggest that compared with sorafenib, patients in the HAIC group have a lower incidence of AEs in the treatment process and higher safety, especially when HCC is combined with portal vein tumor thrombosis [12,27,41]. Both the HAIC group and the sorafenib group, there were cases of discontinuation of treatment due to AEs.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The incidence of HCC in China accounts for more than 55% worldwide . Only 30%‐40% of HCC patients can receive radical treatment, which seriously threatens people's life and health …”
Section: Introductionmentioning
confidence: 99%
“…3 Only 30%-40% of HCC patients can receive radical treatment, which seriously threatens people's life and health. 4 The highest liver cancer rates are found in East and Southeast Asia and in Middle and Western Africa. This difference in incidence of liver cancer between different geographical regions and countries is mainly attributed to difference in the incidence of underlying risk factors.…”
Section: Introductionmentioning
confidence: 99%